Reviewing the TEI ODD system. - Rahtz, S; Burnard, L (ACM, 2013)
For many years the Text Encoding Initiative (TEI) has maintained a specialised high-level XML vocabulary in the 'literate programming' paradigm to define its influential Guidelines, from which schemas or DTDs in other schema languages are derived. This paper reviews the development of this vocabulary, known as ODD (for 'One Document Does it all'). We discuss some problems with the language, and propose solutions to make it more complete and extensible. © 2013 ACM.